Human gastrin- releasing peptide receptor expression in women with uterine cervix cancer - Kunos, Charles A.; Fabian, Denise; Napier, Dana; Stonecypher, Mark S.; Duncan, Ravyn M.; Hurt, Jason (Frontiers in Oncology, 2023)
Introduction: 212Pb-DOTAM-GRPR1 is a pharmaceutical radioimmunoconjugate comprised of an α particle-emitting radionuclide lead-212 (212Pb), a metal chelator DOTAM (1,4,7,10-Tetrakis(carbamoylmethyl)-1,4,7,10-tetraazacyclododecane) and a gastrin-releasing peptide receptor (GRPR)-targeted antagonist currently being evaluated as therapy in uterine cervix and other cancer types. Previous studies have revealed that a variable proportion of uterine cervix cancer tumors overexpress the radiopharmaceutical target GRPR when assessed by cell proportion and staining intensity immunoreactive scores (IRS). A tumor response to 212Pb-DOTAM-GRPR1 strongly associates with GRPR overexpression, and therefore, it seems reasonable to assess uterine cervix cancer GRPR immunoreactivity for greater insight into the feasibility of using 212Pb-DOTAM-GRPR1 as a radiopharmaceutical treatment. Methods: We examined a series of 33 uterine cervix cancer paraffin-embedded tumors in order to establish whether this tumor type overexpresses GRPR at level of an IRS score of 6 or higher, as 212Pb-DOTAM-GRPR1 is currently being evaluated in clinical trials against tumors showing such a level of expression. Results: The results show that 5 of 5 (100%) primary adenocarcinoma and 10 of 16 (63%) primary squamous cell tumors overexpress GRPR at an IRS 6 or higher score. Discussion: The frequency of overexpression in this study suggests that 212Pb-DOTAM-GRPR1 radiopharmaceutical treatment could have value in the management of persistent, recurrent, or metastatic uterine cervix cancer patients. A phase I clinical trial inclusive of metastatic uterine cervix cancer patients is underway (NCT05283330).